Paper angels : a novel - Wayne, Jimmy, 1972- (Howard Books, 2011)
When he picks the name of a teenager from the Salvation Army's Angel Tree program, businessman Kevin Morell, moved and intrigued by Thomas Reed's list, finally discovers the true meaning of Christmas through a random act of kindness.